2020
DOI: 10.1515/jpem-2020-0336
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the genetic and clinical spectrum, including candidate genes, of monogenic diabetes: a multicenter study in South Korea

Abstract: ObjectivesMonogenic diabetes includes a group of heterogeneous diabetes types. We aimed to identify the frequency, clinical and molecular features of monogenic diabetes in a Korean pediatric cohort.MethodsA retrospective cohort and multicenter study of Korean children suspected to have monogenic diabetes, managed by four pediatric endocrine centers in the southeast region of South Korea, from February 2016 to February 2020. We recruited 27 pediatric Korean patients suspected to have monogenic diabetes who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Even after testing for pancreatic beta-cell autoimmune markers, and performing comprehensive targeted NGS, in 8.4% (102/1209) of the total cohort precise diabetes etiology was not identified. As expected, high-throughput sequencing brought several novel variants (11/102) in potential diabetes genes, in agreement with other authors reporting candidate gene variants in up to 10% of sequenced cohorts 26–28. Genomic individualized medicine not only brings the accurate molecular diagnosis and the most effective treatment plan for the patient but also delivers surveillance plan for family members; furthermore, it has proven cost-effectiveness for the healthcare system 29.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Even after testing for pancreatic beta-cell autoimmune markers, and performing comprehensive targeted NGS, in 8.4% (102/1209) of the total cohort precise diabetes etiology was not identified. As expected, high-throughput sequencing brought several novel variants (11/102) in potential diabetes genes, in agreement with other authors reporting candidate gene variants in up to 10% of sequenced cohorts 26–28. Genomic individualized medicine not only brings the accurate molecular diagnosis and the most effective treatment plan for the patient but also delivers surveillance plan for family members; furthermore, it has proven cost-effectiveness for the healthcare system 29.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, high-throughput sequencing brought several novel variants (11/102) in potential diabetes genes, in agreement with other authors reporting candidate gene variants in up to 10% of sequenced cohorts. [26][27][28] Genomic individualized medicine not only brings the accurate molecular diagnosis and the most effective treatment plan for the patient but also delivers surveillance plan for family members; furthermore, it has proven cost-effectiveness for the healthcare system. 29 Therefore, with this study, we also present our selection of potential genes for MD for further functional analysis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when examining Iranian families with diabetes, Sarmadi et al ( 20 ) concluded that the CEL variant p.Ile488Thr causes MODY, even if present at an allele frequency of 0.01 in various Middle Eastern populations. Other single cases or families proposed to carry pathogenic CEL mutations outside the VNTR have been published from India ( 21 ), Siberia ( 22 ), China ( 23 ), and South Korea ( 24 ).…”
Section: Discussionmentioning
confidence: 99%